(untitled) (Albayan Scientific Journal, 2023)
Dipyrone is a non-steroidal anti-inflammatory drug (NSAID), commonly used in the past as a powerful painkiller and fever reducer. It is better known under the brand names Conmel®, Neo-Melubrina®, Magnopyrol®, Prodolina F®, Analgin®, and Novalgin®. Because of the risk of serious adverse effects, its use is justified only in serious situations where no alternative is available or suitable.